A STUDY ON CUTANEOUS ADVERSE DRUG REACTIONS REPORTED IN A TERTIARY CARE HOSPITAL, KANCHIPURAM - PANNEERSELVAM, NITHYA; KADHIRVELU, PARIMALA; SOMASUNDARAM, REVATHI; SOUNDARRAJAN JAYAPRAKASH (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The objective of the study was to study the pattern of various types of cutaneous adverse drug reactions (CADRs) and its relation to therapeutic agents. Methods: A retrospective study was carried out in the Department of Pharmacology, Meenakshi Medical College Hospital and Research Institute. Pharmacovigilance reports collected from 2017 to 2019 which were probable and certain by the WHO causality assessment were included in the study. Descriptive statistics were used. Values were expressed in numbers and percentage. Results: Adverse drug reactions (ADRs) of 40 patients were selected based on the inclusion criteria, of which 22 were female (55%) and 18 males (45%). Patients aged <50 years had more incidence (77.5%) of ADRs. Cutaneous manifestations contributed to major ADRs (67.5%). CADRs were more common with antibiotics (55.5%) followed by nonsteroidal anti-inflammatory drugs (14.6%). Conclusion: The most common therapeutic agent of CADRs were antibiotics (fluoroquinolones and cephalosporins) and the frequent cutaneous manifestation was urticaria.